Study to Evaluate the Management of Adult Calcaneal Fractures Treated with Plating - Divthane, Rupam (Journal of Biomedical and Pharmaceutical Research, 2018)
Background: Calcaneal fractures, often resulting from high-energy trauma, can severely impact foot function and patient mobility. Surgical management, particularly with plating, has become a standard approach for complex and displaced fractures. The clinical importance of evaluating the management of calcaneal fractures with plating lies in improving patient outcomes. Effective management is crucial for restoring foot function, reducing pain, and preventing long-term disability. Historically, calcaneal fractures have been treated using a variety of methods including conservative management with casting, open reduction and internal fixation (ORIF) with conventional plates, and more recently, with locking plates. Conservative management is generally reserved for non-displaced fractures or those that are expected to heal with minimal intervention. The choice of fixation method impacts fracture healing, alignment restoration, and the risk of postoperative complications. Despite the advancements in plating technology, there remains a need for comprehensive evaluation of locking plate fixation in the context of adult calcaneal fractures. Previous studies have highlighted the benefits of locking plates, but more evidence is needed to validate their effectiveness compared to traditional methods, particularly in terms of functional recovery, complication rates, and overall patient satisfaction. Aim: This study aims to evaluate the management of adult calcaneal fractures treated with plating, specifically focusing on the effectiveness of locking plates in terms of fracture stability, alignment restoration, and functional recovery. Material and Method: A prospective cohort study was conducted in the Department of Orthopedics. A total of 60 adult patients with displaced calcaneal fractures were included. All participants underwent surgical treatment with locking plate fixation. Preoperative assessments included detailed imaging for fracture classification according to Sanders’ classification. Postoperative evaluations involved clinical and radiographic assessments at 6 weeks, 3 months, 6 months, and 12 months. Primary outcomes measured were changes in Bohler’s angle, time to radiographic union, and functional recovery as assessed by the American Orthopaedic Foot & Ankle Society (AOFAS) score and Visual Analog Scale (VAS) for pain. Secondary outcomes included the incidence of complications and patient satisfaction.